The Effect of Interdiction on Coca Cultivation in Colombia (2019)
his paper studies the effect of interdiction on coca cultivation in Colombia. Though directed against intermediate and final stages of cocaine production, this strategy could also have an impact on coca cultivation by affecting monopsonistic activities of ilegal groups. My results suggest that different types of interdiction operations have a negative effect on coca crops. In particular, I find that the presence of dismantling of laboratories causes a reduction of 0.003 to 0.006 hectares per squared kilometer in coca cultivation, coca base seizures cause a reduction of 0.003 to 0.008 hectares per squared km, coca leaves seizures cause a reduction of 0.006 to 0.019 hectares per squared km and cocaine seizures cause a reduction of 0.009 to 0.061 hectares per squared km. I interpret these results as evidence that interdiction is an effective anti-narcotic strategy; however,a cost-benefit analysis is needed to evaluate its convenience over other strategies, like aerial spraying campaigns.